Dynamics of Language Attitudes of the Community in the Lasem Chinathown Area - Afifah, Zaimatul; Mualafina, Rawinda Fitrotul; Kurniawan, Latif Anshori (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2026)
Lasem Chinatown is widely recognized as a multicultural space that has united Javanese, Chinese, and Arab communities for centuries. This interaction has shaped diverse linguistic practices, including Indonesian, Javanese, Mandarin, and Arabic. This study aims to describe the dynamics of language attitudes toward these four languages ​​within the context of diglossia. A descriptive qualitative approach was used. Data were collected through interviews with five respondents, field observations, and supporting sources of both direct and online documentation. The researcher became the main instrument assisted by interview guide and observation notes. Data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that the Lasem Chinatown community exhibits positive attitudes toward Indonesian and Javanese, which are used in formal and everyday communication. Conversely, Mandarin has experienced language shift, as it is no longer actively used in social interactions and remains largely symbolic. Meanwhile, Arabic, particularly at the Kauman Islamic boarding school, exhibits positive attitudes in the religious sphere. This suggests that the use of Arabic in the boarding school reflects the continuity of Islamic tradition rather than the presence of Arab ethnicity. Thus, these dynamics highlight the clear functional distribution of languages.